REVIEW: Current Status of Extenders and Cryoprotectants on Fish Spermatozoa Cryopreservation - MUCHLISIN Z. A. (Society for Indonesian Biodiversity, 2005)
An important component of many studies of cryopreservation of fish spermatozoa is the type of extenders and cryoprotectants. The suitability of extenders and cryoprotectants differs from one fish to another. There are many studies have been done in cryopreservation of fish spermatozoa. However, there are few review have been done. This review reveals some aspects of cryopreservation especially the role of extender and cryoprotectant in fish sperm cryopreservation. Fish produce high viscosity of sperm and in some cases only small volume is produced. Before cryopreserved in liquid nitrogen, sperm have to dilute with extenders and for long-term cryopreservation,cryoprotectants are needed to protect the sperm cell from cold and hot shock treatments and prevent cell dehydration during pre-freezing, freezing and post thawed. The suitability of extenders and cryoprotectants differs from one fish to another. Over the last decade, studies on the cryopreservation of mammalian sperm, animal husbandry sperm and human sperm have progressed significantly but studies on fish sperm is still confined to some aquatic.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: fish, sperm, cryopreservation, extenders, cryoprotectants